Do Stem Cells Have an Effect When We Fat Graft?. (June 2016) - Rinker, Brian D.; Vyas, Krishna S.
Abstract : Abstract: Fat grafting has become a widely accepted modality of soft tissue restoration and has found applications in many areas of aesthetic and reconstructive plastic surgery. Numerous claims have been made regarding the regenerative effects of fat grafting on the recipient bed. The purpose of this paper is to survey the available literature to answer the question of whether fat grafting has a positive effect on the surrounding tissues. It has been convincingly demonstrated that fat grafts contain viable adipose-derived stem cells (ASCs). The fate of these cells is determined by the microenvironment of the recipient bed, but animal studies have shown that a large fraction of ASCs survive engraftment. Numerous clinical studies have demonstrated the positive effects of fat grafting on recipient tissues. Improvement in validated scar scores as well as scar stiffness measurements have been documented after fat grafting of burn scars. Fat grafting has also been convincingly demonstrated to improve the quality of irradiated tissues, as measured by validated clinical scales and staged histology. It is ultimately unclear whether ASCs are responsible for these effects, but the circumstantial evidence is weighty. Fat grafting is effective for volumizing and improving skin quality in the setting of radiation, burns, and other scars. The observed effects are likely due to ASCs, but the evidence does not support the routine use of ASC-enriched fat grafts.